2012
DOI: 10.1007/s10816-012-9132-9
|View full text |Cite
|
Sign up to set email alerts
|

Other People’s Data: A Demonstration of the Imperative of Publishing Primary Data

Abstract: Many scholars avoid employing "legacy" datasets, even if accessible, because of perceived unknowns in using data collected by others. This study explored issues in using data generated by other analysts. Three researchers independently analyzed a legacy, decades-old zooarchaeological dataset and then compared their analytical approaches and results. Although they took a similar initial approach to determine the dataset's suitability for analysis, the three researchers generated markedly different interpretive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
99
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(103 citation statements)
references
References 20 publications
0
99
0
1
Order By: Relevance
“…Even more importantly, some data cannot be recollected or reproduced. Therefore, adequate documentation of research data is an essential part of RDM for future sharing and reuse (Atici et al 2013, 670, Chavan and Penev 2011, 2, Costello 2009, 421, Kansa and Kansa 2013, 4, Kratz and Strasser 2014, 4, Niu and Hedstrom 2008, 4, Rees 2010). …”
Section: Literature Reviewmentioning
confidence: 99%
“…Even more importantly, some data cannot be recollected or reproduced. Therefore, adequate documentation of research data is an essential part of RDM for future sharing and reuse (Atici et al 2013, 670, Chavan and Penev 2011, 2, Costello 2009, 421, Kansa and Kansa 2013, 4, Kratz and Strasser 2014, 4, Niu and Hedstrom 2008, 4, Rees 2010). …”
Section: Literature Reviewmentioning
confidence: 99%
“…The use of modern digital media has the power to do so Marwick et al 2017;Wilson and Edwards 2015). Our baseline assumption is that we need to record data more consistently in the field and to release them in full as structured open data since archaeological excavations are a public good that should be shared, and the primary data from the excavation are necessary for making advancement in the discipline (Atici et al 2013;Kansa and Whitcher-Kansa 2013). Scientific elaboration is hampered not only by limited access to research data but also by the fact that, in most cases, the data are not ready for digital processing.…”
Section: Going Openmentioning
confidence: 99%
“…The sheer volume of burial data available, and questions of how to extract and ultimately analyse these data in a way which produces valuable information, is what lies at the heart of this project. As Atici et al (2012) have suggested, it is pivotal that we, as archaeologists, develop strategies for best use of "legacy data" which are transparent and ultimately transferable. By necessity, the approaches to this problem for Britain and the Levant have had to be different (Table 2 and see Figure 1a 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 number of recordable individuals involved may be somewhere in the region of 100,000, whilst the number of mortuary sites may be around 10,000.…”
Section: Insert Table 1 Herementioning
confidence: 99%